2022
DOI: 10.3389/fgene.2022.967696
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of tanning response to sun exposure on the risk of skin diseases through Mendelian randomization

Abstract: Background: Until now, the relevance of the tanning response to sun exposure and skin diseases has incomplete and inconsistent epidemiological observations. In this case, it is valuable to find out the causality of tanning response to sun exposure and skin diseases, and take a step further toward developing effective therapies as well as prevention methods.Methods: We investigated the causal effect of tanning response to sun exposure on 10 major skin diseases that have been studied in recent large-scale genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…However, a recent Mendelian randomization analysis on the role of ease of skin tanning on nine major skin diseases, including melanoma, has supported the causative role of ease of skin tanning on CM. Despite its smaller sample size, this study also observed a similar causal relationship between the ease of skin tanning and an elevated risk of melanoma 32 . The discrepancy between epidemiological and MR research concerning the reported correlation between tanning predilection and melanoma awaits future investigations.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…However, a recent Mendelian randomization analysis on the role of ease of skin tanning on nine major skin diseases, including melanoma, has supported the causative role of ease of skin tanning on CM. Despite its smaller sample size, this study also observed a similar causal relationship between the ease of skin tanning and an elevated risk of melanoma 32 . The discrepancy between epidemiological and MR research concerning the reported correlation between tanning predilection and melanoma awaits future investigations.…”
Section: Discussionsupporting
confidence: 54%
“…Despite its smaller sample size, this study also observed a similar causal relationship between the ease of skin tanning and an elevated risk of melanoma. 32 The discrepancy between epidemiological and MR research concerning the reported correlation between tanning predilection and melanoma awaits future investigations. To unmask the actual cause and effect, larger GWAS summary statistics should be obtained for different ethnic groups, focusing on skin tanning response to UVR and sun exposure-related habits.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have indicated that certain individuals who exhibit a tanning response to sunlight exposure may have an increased risk of developing skin diseases. However, the research exploring the potential impact of gut microbiota on the relationship between skin tanning and skin cancer is currently lacking ( 28 ).…”
Section: Introductionmentioning
confidence: 99%